2014
DOI: 10.3390/ijerph110202346
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital ECG E-Transmission for Patients with Suspected Myocardial Infarction in the Highlands of Scotland

Abstract: Patients with ST elevation myocardial infarction (STEMI) require prompt treatment, best done by primary percutaneous coronary intervention (PPCI). However, for patients unable to receive PPCI, immediate pre-hospital thrombolysis (PHT) is the best alternative. Evidence indicates that diagnostic and management support for staff increases the use of PHT. This study aimed to describe the patient demographics and management of patients, to determine any potential inter-area differences in referral rates to the ECG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…One of the most important activities in the protection of human life is the intervention of emergency responders, for which an important issue in the unpredictable urban road networks is the time required for an emergency vehicle to reach an event scene. Congestion and the various obstacles that may appear during the journey on the chosen path can increase travel time and therefore reduce the chances of ensuring the safety of human life (Blackwell et al, 2002;Pons et al 2005;Sladjana et al 2011;Rushworth et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important activities in the protection of human life is the intervention of emergency responders, for which an important issue in the unpredictable urban road networks is the time required for an emergency vehicle to reach an event scene. Congestion and the various obstacles that may appear during the journey on the chosen path can increase travel time and therefore reduce the chances of ensuring the safety of human life (Blackwell et al, 2002;Pons et al 2005;Sladjana et al 2011;Rushworth et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of emergency medical service (EMS) teams, which are often the first care givers at accident scenes, include: (a) on-site medical treatment for patients with serious or emergency injuries; (b) emergency aid en route to a hospital; and (c) referrals for patients with major injuries living on outlying islands and in remote areas [ 5 ]. A large number of studies have shown that the rapid arrival of emergency vehicles (EVs) and the provision of emergency treatment at accident scenes are critical to reducing incidents of death and disability for acute and critically ill patients [ 6 , 7 , 8 , 9 , 10 , 11 ]. For cardiac arrest patients, survival rates are approximately 43% when basic life support is implemented within 4 minutes, and when advanced cardiac life support is provided within 8 minutes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a precedent from another condition: the Scottish Ambulance Service and general practitioners administer thrombolysis for acute myocardial infarction following advice from coronary care staff assessing ECGs transmitted from ambulances or primary care settings 26 . As such, similar treatment pathways and protocols are already in place for other conditions in potentially life-saving emergencies.…”
Section: Ultrasound Operatorsmentioning
confidence: 99%
“…Poor connectivity in rural areas of the Scottish Highlands has been shown to be a barrier for electrocardiogram (ECG) transmission from ambulances 26 . The size of an ECG data file is vastly smaller than the size of file, or data stream that would be required for ultrasound imagery.…”
Section: Technology To Access Remote Expert Advice In Pre-hospital Stmentioning
confidence: 99%